NAVIGATING THE CHALLENGES OF LANGUAGE INTERFERENCE: STRATEGIES FOR PREVENTION AND OVERCOMING - Doston Ubaydullaev Ziyodulla o`g`li; Zilola Abdurakhmanova Yoqubjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation This comprehensive article explores the intricate landscape of language interference, a common phenomenon in multilingual settings. It addresses the various types and causes of interference, emphasizing the problems associated with this linguistic challenge. The prevention strategies outlined, including cultural awareness training and immersion programs, aim to create a solid foundation for language learners. The section on overcoming interference provides practical solutions, emphasizing the importance of targeted error correction and individualized learning plans. In conclusion, the article highlights the significance of embracing linguistic diversity and implementing effective strategies to enhance communication and language proficiency.